Women's aggressive fantasies : a post-Jungian exploration of self-hatred, love and agency - Austin, Sue (Routledge, 2005)
Drawing together apparently disparate strands of theory from feminism, critical psychology, contemporary psychoanalysis and post-Jungian thought, this books succeeds in providing a new insight into the phenomenon of female violence and aggression.